Knowledge Management System Based on Knowledge Grid in Business Organization - Durman, Agnieszka (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
In this paper architecture and problems of knowledge management systems in business organizations are discussed. The objective of this paper is to show that a new architecture of Knowledge Management System based on Knowledge Grid could be a good proposal as a tool for more knowledge effective and efficient management. In this paper, a new model is proposed. This model should show how it could be possible to create and distribute knowledge within Knowledge Grid.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 25, s. 56-64